Cognitive behavior therapy counseling to reduce adolescent grief after the death of a parent - Novianti, Herny; Ruhansih, Dea Siti; Ahman, Ahman (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Grief is the physical, psychological, social, and spiritual reaction to a significant loss in one's life. This study aims to obtain an empirical description and analysis of the effectiveness of Cognitive Behaviour Therapy Counseling (using cognitive restructuring technique) in reducing the respondent's grief about the death of her parents who died due to the oil refinery fire in Balongan. Through this counseling, the respondence is able to: a) identify patterns of interaction of behavior, thoughts, and emotions; b) identify core beliefs, cognitive distortions, and automatic thoughts; c) identify thinking errors in herself; and d) change the cognitive distortions her experiences. The research method used in this research is Single Subject Design. This research uses quantitative analysis techniques using the formula 2 standard deviations which shows that cognitive behavioral therapy. The results of this research show that the counseling applied can be used to overcome the sadness that exists in respondents, including the ability to apply psychological, physical and social aspects.